Principles of group fitness instruction - McGill, Erin A. (Jones & Bartlett Learning, 2019)
"Since 1983, AFAA has pioneered and set the fundamental movement standards in the fitness industry. With more than 350,000 certifications issued in 73 countries, AFAA-trained instructors have motivated millions of people toward healthier and happier lives. Through this course, you will acquire the knowledge and practical skills needed to inspire positive life changes as a group fitness instructor. Whether your clients are interested in dance, resistance training, yoga, mat pilates, indoor cycling or cardio, you'll be prepared with the foundation needed to lead any group with confidence. This textbook includes all the latest science on human movement and exercise, plus over 30 years of insights straight from the experts. The easy-to-read format supports a multi-layered learning experience with a focus on real-life application" --